Prototype of Ship Fuel Monitoring System Using NodeMCU - Anggara Trisna Nugraha; Chusnia Febrianti (Journal of Marine Electrical and Electronic Technology, 2024)
The prototype ship fuel monitoring system is designed to enhance the efficiency and effectiveness of fuel management in container shipping operations. Fuel costs account for approximately 70% of a ship's operating expenses, making it imperative for shipping companies to implement strict fuel usage monitoring to minimize waste and optimize consumption. The absence of an automated fuel consumption monitoring system often results in management inefficiencies, such as inaccurate tracking and unplanned corrective actions to address fuel discrepancies. This research introduces a solution by employing ultrasonic level sensors integrated with an Outseal PLC, which gathers real-time fuel level data. The data is transmitted to a web server via NodeMCU ESP32, enabling continuous access and monitoring for stakeholders. Calibration tests revealed that the ultrasonic sensors achieve an average error rate of 0.037%, 0.02%, 0.043%, and 0.047%, showcasing their high accuracy and reliability. The findings confirm that the proposed system effectively facilitates real-time monitoring of fuel usage, offering enhanced operational transparency, reduced waste, and optimized fuel management for maritime applications. This research contributes significantly to the field of engineering and maritime operations by providing a robust and scalable system for fuel monitoring based on NodeMCU.